Metformin - Pharmacology and Drug Interactions 2021
DOI: 10.5772/intechopen.99815
|View full text |Cite
|
Sign up to set email alerts
|

Metformin: Pros and Cons

Abstract: Metformin was approved for the treatment of Type 2 Diabetes Mellitus in 1958 for UK, in 1972 for Canada and in 1995 by FDA in USA. Metformin is the drug of choice for patients who are obese and have type 2 diabetes mellitus. Though metformin was at first proven to treat hyperglycemia, many other uses of metformin are proven to be effective. It is also used for gestational diabetes mellitus, obesity, hyper secretion of ovarian androgen, poly-cystic ovary syndrome (PCOS), anti-psychotic therapy induced weight ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 116 publications
0
2
0
Order By: Relevance
“…Metformin can lower plasma glucose levels and reduce the amount of glucose absorbed by the body and the amount of glucose produced by the liver. Metformin also enhances tissue sensitivity to insulin [ 190 ]. The substantial role of metformin by numerous mechanisms in various illnesses has been reported [ 191 193 ].…”
Section: Drugs With Antiaging Propertiesmentioning
confidence: 99%
“…Metformin can lower plasma glucose levels and reduce the amount of glucose absorbed by the body and the amount of glucose produced by the liver. Metformin also enhances tissue sensitivity to insulin [ 190 ]. The substantial role of metformin by numerous mechanisms in various illnesses has been reported [ 191 193 ].…”
Section: Drugs With Antiaging Propertiesmentioning
confidence: 99%
“…It is the first-line monotherapy for the treatment of T2DM [18]. Metformin does not enhance insulin secretion which is associated with a lower risk of hypoglycemia [19]. Several studies have demonstrated the benefits of metformin use for the prevention and treatment of GDM.…”
Section: Introductionmentioning
confidence: 99%